Dry-Lensectomy Assisted Lensectomy in the Management for End-Stage Familial Exudative Vitreoretinopathy Complicated With Anterior Segment Abnormalities - Peng, Jie; Zhao, Ziwei; Zou, Yihua; Zhang, Xuerui; Yang, Yuan; Huang, Qiujing; Xu, Mingpeng; Xu, Yu; Zhao, Peiquan (Frontiers in Medicine, 2022)
Purpose: To report a modified technique of dry-lensectomy assisted lensectomy in the management of end-stage familiar exudative vitreoretinopathy (FEVR) complicated with capsule-endothelial, iris-endothelial adhesion and secondary glaucoma. Methods: 24 eyes of 16 patients with severe complications of advanced pediatric total retinal detachment caused by FEVR who received limbus-based dry-lensectomy were studied retrospectively. Preoperative and postoperative clinical information was collected and reviewed. Results: Among the 24 eyes, three eyes (12.50%) underwent lensectomy combined with vitrectomy and membrane peeling simultaneously. 21 (87.50%) eyes underwent staged-lensectomy due to severe corneal opacity or retinal vascular activity, of which eight underwent another vitrectomy combined with membrane peeling. At the last visit (mean:13.86± 5.24 months of follow-up), all eyes had a reconstructed anterior chamber with normal depth. Among 21 eyes having preoperative corneal opacity, 15 (71.43%) had a clearer cornea with reduced opacity, 5 (23.81%) showed similar corneal opacification without deterioration. Among 11 eyes undergone retrolental fibroplasia peeling, six (54.55%) eyes showed partial retinal reattachment in open-funnel type. Conclusion: Dry-lensectomy offered a simple way to lower the IOP and simplified the surgery, which helped to solve the severe anterior segment complications and offer a chance for following retrolental fibroplasia peeling and potential visual gain for selected end-stage FEVR patients.